Discovery of a Highly Selective Glycogen Synthase Kinase‐3 Inhibitor (PF‐04802367) That Modulates Tau Phosphorylation in the Brain: Translation for PET Neuroimaging. (29th June 2016) - Liang, Steven H.; Chen, Jinshan Michael; Normandin, Marc D.; Chang, Jeanne S.; Chang, George C.; Taylor, Christine K.; Trapa, Patrick; Plummer, Mark S.; Para, Kimberly S.; Conn, Edward L.; Lopresti‐Morrow, Lori; Lanyon, Lorraine F.; et al.
Abstract: Glycogen synthase kinase‐3 (GSK‐3) regulates multiple cellular processes in diabetes, oncology, and neurology. N ‐(3‐(1H‐1, 2, 4‐triazol‐1‐yl)propyl)‐5‐(3‐chloro‐4‐methoxyphenyl)oxazole‐4‐carboxamide (PF‐04802367 or PF‐367) has been identified as a highly potent inhibitor, which is among the most selective antagonists of GSK‐3 to date. Its efficacy was demonstrated in modulation of tau phosphorylation in vitro and in vivo. Whereas the kinetics of PF‐367 binding in brain tissues are too fast for an effective therapeutic agent, the pharmacokinetic profile of PF‐367 is ideal for discovery of radiopharmaceuticals for GSK‐3 in the central nervous system. A 11 C‐isotopologue of PF‐367 was synthesized and preliminary PET imaging studies in non‐human primates confirmed that we have overcome the two major obstacles for imaging GSK‐3, namely, reasonable brain permeability and displaceable binding.